PHILIPPINE â€“ US DEFENSE COOPERATION: THE IMPLEMENTATION OF â€œTHE ENHANCED DEFENSE COOPERATION AGREEMENTâ€ TO RESPOND CHINAâ€™S ASSERTIVENESS IN THE SOUTH CHINA SEA (2010 â€“ 2016) - Reynaldo Rudy Kristian Montolalu; Banyu Perwita (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2019)
China assertiveness in the South China Sea has considered as part of its national ambition to dominate most of the sea area as stated in its claim on the â€œnine-dashed lineâ€. This China assertiveness could be seen in its more active policy by projected military power in area disputing. As one of the claimant states, the Philippine felt that Chinaâ€™s actions toward the region have harmed their territorial sovereignty over the West Philippine Sea. The disputed matter between the Philippine and China count active to flare up from 2010 to 2016 which marked with several incidents between both of the countries navies in Scarborough Shoal and Second Thomas Shoal. In response to the condition in the South China Sea, the Philippine was trying to enhance their defense posture which considered weak through AFP Modernization Pact initiated by President Benigno Aquino III at the beginning of his administration. Constrained by military budget allowance and limited defense equipment, the Philippine is relying on its military alliance which is the United States that has been created since a long period of time, especially in order to enhance the Philippine external defense. In 2014, both of the countries signed the Enhanced Defense Cooperation Agreement (EDCA) which is the enhancement of the previous defense cooperation agreements: the Mutual Defense Treaty 1951 and the Visiting Forces Agreement 1998. This new defense cooperation agreement considered to play a significant role in supporting Philippineâ€™ effort on responding the internal and external threats, including the unpredictable China militarization in the South China Sea. Keywords: South China Sea, China Assertiveness, Defense Cooperation, The Philippine â€“ US bilateral relations, Enhanced Defense Cooperation Agreement (EDCA) Abstrak Keagresifan Cina di Laut Cina Selatan merupakan suatu ambisi nasionalnya untuk menguasai sebagian besar wilayah laut sebagaimana tertuang dalam â€œSembilan Garis Putus-Putusâ€. Bentuk keagresifan Cina ini terlihat dalam kebijakannya yang lebih aktif dengan cara memproyeksikan kekuatan militer di daerah yang masih disengketakan. Sebagai salah satu negara yang bersengketa, Filipina merasa tindakkan yang dilakukan Cina dikawasan telah merugikan kedaulatan teritorinya yaitu Laut Filipina Barat. Masalah sengketa Filipina dan Cina terhitung aktif bergejolak sejak 2010 hingga 2016 yang ditandai dengan beberapa insiden antara kapal angkatan laut kedua negara di Scarborough Shoal dan Second Thomas Shoal. Menanggapi kondisi di Laut Cina Selatan, Filipina mencoba memperkuat postur pertahanannya yang masih lemah melalui Pakta Modernisasi Angkatan Bersenjata Filipina yang diinisiasi oleh Presiden Benigno Aquino III pada awal masa pemerintahannya. Terkendala masalah anggaran belanja dan keterbatasan alutsista, Filipina mengandalkan aliansi militernya dengan Amerika Serikat yang sudah terbentuk sejak lama, terlebih khusus dalam upaya memperkuat pertahanan eksternal Filipina. Pada tahun 2014, kedua negara menandatangani Perjanjian Peningkatan Kerjasama Pertahanan (EDCA) yang merupakan peningkatan dari perjanjian kerjasama pertahanan yang telah terbentuk, yaitu Perjanjian Pertahanan Bersama 1951 dan Perjanjian Kunjungan Pasukan 1998. Perjanjian kerjasama pertahanan yang baru ini dianggap dapat membantu Filipina dalam upaya melawan ancaman internal dan eksternal termasuk militerisasi Cina di Laut Cina Selatan yang sulit untuk diprediksi. Kata Kunci: Laut Cina Selatan, keagresifan Cina, kerjasama pertahanan, hubungan bilateral Filipina dan Amerika Serikat, Enhanced Defense Cooperation Agreement (EDCA)